No beneficial effect of all-trans retinoic acid in previous non-responder patients with chronic hepatitis C: the ATRACTION study, a phase II randomised trial - Schuchmann, Marcus; Kittner, Jens M.; Schlaak, Jörg F.; Klass, Dietmar M.; Eisenbach, Christoph; Berg, Thomas; Trautwein, Christian; Günther, Rainer; Zeuzem, Stefan; Gösseringer, Roger; Ehrlich, Anne; Neumann, Konrad; et al. (Digestive and liver disease, 2013)
Background - Preclinical data suggested all-trans retinoic acid (tretinoin) as a potential antiviral agent against chronic hepatitis C infection. - Aims - To assess efficacy, safety, and tolerability of tretinoin in combination with peg-interferon and ribavirin in genotype-1 infected patients with prior non-response. - Method - We performed an open-label multicentre clinical trial. Patients were randomised to either receive additional tretinoin (45mg/m2/day) for 12 weeks (arm A), or peg-interferon and ribavirin alone (arm B). Primary endpoint was the slope of the third phase of viral decline (Mδ) as determined in an established kinetic model known to correlate with treatment outcome. Secondary endpoints were additional kinetic parameters, viral response rates, safety, and tolerability. - Results - 27 patients in arm A and 30 patients in arm B were treated per protocol until week 12. Viral kinetic parameters did not differ. Rates of early virological response (>2log10 drop at week 12) were similar (10/27 versus 11/30 patients). In arm A, patients experienced a higher rate and intensity of adverse events, most commonly skin and mucosal dryness, and headache. - Conclusion - Addition of tretinoin was safe and acceptably well tolerated. However, it did not influence viral kinetics and thus cannot be further considered as a treatment option.